Tingkat Pengetahuan tentang Anemia dan Hubungannya dengan Kepatuhan Konsumsi Tablet Fe pada Remaja Putri di MTS Raudhatul Muta’allimin Tahun 2021: Level of Knowledge about Anemia and its Relationship to Compliance with Consumption of Fe Tablets in Young Girls at MTS Raudhatul Muta'allimin in 2021 - Melinda, Tryanova; Rina Afrina; Wesley Dailey (MPI Press, 2023)
Introduction: Adolescence is a period that is passed in every individual development, adolescent development is a period of individual development which is a period of achieving mental, emotional, social, physical and escape patterns from childhood to adulthood. Objectives: To find out the relationship between the level of knowledge about anemia and the compliance with consumption of Fe tablets in young women at MTs Raudhatul Muta'allimin in 2021. Methods: The research design used is correlation analytic with a cross-sectional correlation or cross-sectional approach. Cross-sectional approach. The population in this study were female students at MTs Raudhatul Muta'allimin 75 people. The sample calculation in this study was total sampling. The sample inclusion criteria in this study were young women who attended school at MTs Raudhatul Muta'allimin in 2021. The instrument used a questionnaire. In this study, the Chi-square or qai-square test was used to see the dependence between the independent variables and the dependent variable on a nominal or ordinal scale. Results: The results of the bivariate analysis of the level of knowledge of anemia showed p = 0.000, and the bivariate analysis of adherence to Fe tablet consumption showed p = 0.000. Conclusion: Based on the results of research on the relationship between the level of knowledge about anemia and adherence to Fe tablet consumption in adolescent girls at MTs Raudhatul Muta'allimin in 2021.